Changing opinions about research by Saudi medical students - Abulaban, Ahmad (Adv Med Educ Pract, 2017)
OBJECTIVE: The objective of this study was to investigate and compare the opinions and attitudes of medical students toward medical research in five Saudi universities and examine the changes observed in these opinions and attitudes in one of these universities over a period of time. METHODS: This is a cross-sectional study conducted among medical students in five Saudi universities. This study was based on a survey undertaken in 2015. The survey consisted of five questions inquiring about the opinions and attitudes of medical students toward medical research. The same survey was carried out 8 years earlier in one of these universities (King Abdulaziz University [KAU]), and the results obtained during the two periods (2007 and 2015) were compared. RESULTS: A convenient sample of 924 students was selected from five Saudi universities. Ninety-five (10.3%) of the medical students were not aware of the usefulness and importance scientific research will have on their future careers. A total of 409 (44.3%) stated that they had no knowledge on how to conduct scientific research. On the other hand, a vast majority of medical students (98.1%) expressed a willingness and interest to participate in scientific research if provided with an opportunity. The percentage of students from KAU strongly agreeing to participate in research rose from 33.1% in 2007 to 81.5% in 2015 (P=0.001). Of all the students surveyed, 431 (46.6%) had participated in scientific research as undergraduates. CONCLUSION: Most students in five Saudi universities expressed enthusiasm for participating in a research project, but only a few of them had sufficient knowledge on basic research. There was considerable improvement in students’ perception of research in KAU when comparing their responses in 2007 to those in 2015.